Pengasuhan Single Mother dan Dampaknya Terhadap Perkembangan Psikososial Anak Usia Dini: A Systematic Literature Review : Single Mother Parenting and Its Impact on Early Childhood Psychosocial Development: A Systematic Literature Review - Bintang Shafa Masnaini. Z; Suyadi; Rohinah (Universitas Ngudi Waluyo, 2026)
Global changes in family structure have led to a growing number of single-mother households, raising important concerns regarding parenting practices and early childhood psychosocial development. This study aims to systematically review empirical evidence on single mother parenting and its impact on the psychosocial development of early childhood using a Systematic Literature Review (SLR) approach. Literature research was conducted across Scopus, PubMed, and Google Scholar databases via Publish or Perish, following the PRISMA guidelines. A total of 26 eligible studies were critically analyzed and synthesized. The findings indicate that single mother parenting occurs within complex structural and psychosocial contexts characterized by economic strain, dual caregiving and breadwinning roles, parenting stress, and limited social support as major risk factors. These conditions are associated with increased risks of emotional regulation difficulties, externalizing behaviors, and social adjustment problems in early childhood. However, the review also highlights significant protective factors, including social support, democratic parenting styles, warm mother–child communication, and adaptive coping strategies, which contribute to child and family resilience. Overall, the findings emphasize that the quality of parenting processes plays a more decisive role in shaping children’s psychosocial outcomes than family structure alone. This review contributes to a non-deficit perspective on single mother families and provides empirical insights to inform policy development and intervention programs aimed at strengthening parenting capacity and promoting early childhood well-being. ABSTRAK Perubahan struktur keluarga global ditandai dengan meningkatnya jumlah keluarga single mother, yang membawa implikasi signifikan terhadap pengasuhan dan perkembangan psikososial anak usia dini. Penelitian ini bertujuan untuk mengkaji secara sistematis temuan-temuan empiris terkait pengasuhan single mother serta dampaknya terhadap perkembangan psikososial anak usia dini melalui pendekatan Systematic Literature Review (SLR). Proses penelusuran literatur dilakukan pada basis data Scopus, PubMed, dan Google Scholar melalui aplikasi Publish or Perish, dengan mengacu pada pedoman PRISMA. Sebanyak 26 artikel yang memenuhi kriteria inklusi dianalisis dan disintesis secara kritis. Hasil kajian menunjukkan bahwa pengasuhan single mother berlangsung dalam konteks struktural dan psikososial yang kompleks, ditandai oleh tekanan ekonomi, peran ganda ibu, stres pengasuhan, dan keterbatasan dukungan sosial sebagai faktor risiko utama. Faktor-faktor tersebut berhubungan dengan peningkatan risiko masalah regulasi emosi, perilaku eksternalisasi, dan kesulitan sosial pada anak usia dini. Namun demikian, temuan juga menegaskan adanya faktor protektif yang signifikan, seperti dukungan sosial, pola asuh demokratis, komunikasi ibu–anak yang hangat, serta strategi koping adaptif, yang mampu memperkuat resiliensi anak dan keluarga. Kajian ini menyimpulkan bahwa kualitas proses pengasuhan lebih menentukan perkembangan psikososial anak dibandingkan struktur keluarga itu sendiri. Temuan penelitian ini berkontribusi pada penguatan perspektif non-defisit dalam kajian single mother serta memberikan dasar empiris bagi pengembangan kebijakan dan intervensi yang berorientasi pada penguatan kapasitas pengasuhan dan kesejahteraan anak usia dini.